Ensuring Safety of Patients in Complex Health Systems: A Focus on Primary Healthcare Service Relations in Nigeria. - Uzochukwu, Benjamin; Agwu, Prince; Okeke, Chinyere; Uzochukwu, Adaora; Onwujekwe, Obinna (Health & Social Work, 2023)
Patient-centered healthcare is a goal for all health systems. However, given the inherent complexities of the health system as one with many nonlinear and dynamic components, the safety of patients could be affected. Therefore, there is the need to study these complexities to manage them toward optimal service delivery. The present study is a qualitative inquiry into the complexities of primary healthcare (PHC) in Nigeria and effects on patients' safety across four PHC facilities in Enugu state in southeast Nigeria. It utilizes a framework that draws on the components of interprofessional collaboration, inclusive of health financing and health workforce satisfaction, to understand the complex PHC system and patient safety. The study findings show that the PHC system in the study area performs suboptimally on the three counts, which implies poor management of the complexities of the system such that patients are highly susceptible to harm. Making a commitment to addressing the shortcomings present in each of the three components will help to decomplexify PHC in line with the World Health Organization agenda of achieving resilient and strong health systems. Importantly, optimizing the psychosocial space in Nigeria's PHC by employing qualified social workers and other psychosocial professionals is crucial for patient safety and a range of psychosocial activities that can enhance job satisfaction of health workers.